Adjustment of biomass product gas to raise H2/CO ratio and remove tar over sodium titanate catalysts. (January 2018) - Yuan, Hongyou; Wu, Shubin; Yin, Xiuli; Huang, Yanqin; Guo, Daliang; Wu, Chuangzhi
Abstract: To raise H2 /CO and remove tar for biomass product gas, sodium titanates 4Na2 O·5TiO2 and Na2 O·3TiO2 were evaluated at 850 °C using wood powder pyrolysis gas produced from a 0.3 kg/h screw pyrolyzer with no extra steam, silica sand was selected as an inert material for comparison. The GHSV of the runs were around 2000 h −1 with tar content of about 200 g/Nm 3 . The results suggest that 4Na2 O·5TiO2 presents the highest activity, Na2 O·3TiO2 ranks slightly lower, and silica sand shows no activity of enhancing hydrogen yield. The hydrogen formation is promoted through tar cracking, water gas shift and/or methane reforming. The H2 /CO increases to 1.8–2.0, which is higher than that of silica sand (about 0.35) and raw gas (about 0.25). Tar conversion in the 4Na2 O·5TiO2 reforming was about 99% and nearly no coke was formed within the test duration of about 8 h, whereas the silica sand was coked obviously in 1 h. Most tar components can be effectively reformed, except for parts of xylene, naphthalene, biphenylene, and anthracene. The activity of 4Na2 O·5TiO2 decreases gradually in the long-term test because of the release of sodium and has a tendency to transform to Na2 O·3TiO2, the latter exhibits satisfactory stability and activity. Highlights: Alkali metal titanate catalysts were prepared for biomass pyrolysis raw gas reforming. The catalysts were evaluated using continuous pyrolysis raw gas with no extra steam. 4Na2 O·5TiO2 and Na2O·3TiO2 present good activity and coke resistance. 4Na2 O·5TiO2 shows the better activity, and Na2 O·3TiO2 exhibits the better stability. H2 formation is promoted because of tar cracking, water gas shift and CH4 reforming.